2017
DOI: 10.1021/acsnano.7b03290
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Electrocatalytic Hydrogen Evolution Reaction on Nitrogen-Doped Carbon Nanosheets with Secondary Heteroatoms

Abstract: Dual heteroatom-doped carbon materials are efficient electrocatalysts via a synergistic effect. With nitrogen as the primary dopant, boron, sulfur, and phosphorus can be used as secondary elements for co-doped carbons. However, evaluation and analysis of the promotional effect of B, P, and S to N-doped carbons has not been widely researched. Here we report a robust platform that is constructed through polydopamine to prepare N,B-, N,P-, and N,S-co-doped carbon nanosheets, characterized by similar N species con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
206
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(212 citation statements)
references
References 50 publications
(109 reference statements)
4
206
1
1
Order By: Relevance
“…In particular, they clearly pointed out, theoretically and experimentally, the well-confirmed B, N-codoped graphene had the highest catalytic capability with the optimized ratio between B, C, and N of 12:77:11 among all the BCN samples (Figure 4c,d). [84] It was found that S codoping maximized the HER performance, followed by P, whereas B codoping decreased the catalytic activity of the N-doped carbons, due to delicate effects of the secondary heteroatom-doping on electronic structures of the catalytic active sites (Figure 4f). [84] It was found that S codoping maximized the HER performance, followed by P, whereas B codoping decreased the catalytic activity of the N-doped carbons, due to delicate effects of the secondary heteroatom-doping on electronic structures of the catalytic active sites (Figure 4f).…”
Section: Carbon Nanomaterials Codoped/multidoped With Heteroatomsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, they clearly pointed out, theoretically and experimentally, the well-confirmed B, N-codoped graphene had the highest catalytic capability with the optimized ratio between B, C, and N of 12:77:11 among all the BCN samples (Figure 4c,d). [84] It was found that S codoping maximized the HER performance, followed by P, whereas B codoping decreased the catalytic activity of the N-doped carbons, due to delicate effects of the secondary heteroatom-doping on electronic structures of the catalytic active sites (Figure 4f). [84] It was found that S codoping maximized the HER performance, followed by P, whereas B codoping decreased the catalytic activity of the N-doped carbons, due to delicate effects of the secondary heteroatom-doping on electronic structures of the catalytic active sites (Figure 4f).…”
Section: Carbon Nanomaterials Codoped/multidoped With Heteroatomsmentioning
confidence: 99%
“…[84][85][86][87][88][89] Of particular importance, Zhang et al, reported the first N and P codoped nanocarbon foams with a mesoporous structure (NPMC) under different pyrolysis temperatures (e.g., NPMC-1000 or NPMC-1100, as shown in Figure 5a,b) as efficient bifunctional catalysts for ORR and OER (Figure 5c) in high-performance Zn-air batteries, including the primary and rechargeable ones. This significant advantage allows for the design of new C-MFCs capable of catalyzing different (electro)chemical reactions simultaneously, such as the ORR, OER, HER, attractive for integrated clean energy technologies, such as metal-air batteries, water splitting, and their integrations.…”
Section: Carbon Nanomaterials Codoped/multidoped With Heteroatomsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because increased numbers of dopant heteroatoms and electronic interactions between different doped heteroatoms often generate additional synergistic effects than single heteroatom-doped counterparts [104]. With N as the primary dopant, B, S, and P can be used as secondary elements for co-doping carbon [4,105]. Here, it was found that S-doping, followed by P-doping, greatly promotes HER.…”
Section: Heteroatom-dopingmentioning
confidence: 95%
“…Further, intertwined N‐CNTs and rough surface on the polyhedron frameworks play critical role in the enhanced performance due to superior conductivity and significant exposure active sites in the harsh electrolyte condition ,. The larger amount of N‐doping in carbon ring can increase the binding energy and improve the stability during HER . Moreover, nitrogen has a chemical interaction with the nearby carbon/metal cores and changes their electronic states, including the structural defects in the carbon matrix …”
Section: Resultsmentioning
confidence: 99%